2005
DOI: 10.1080/14631370500052233
|View full text |Cite
|
Sign up to set email alerts
|

EMU Enlargement to Include CEE Countries: Risks of Sector-based and Geographical Asymmetric Shocks

Abstract: Future membership of CEE countries in the euro zone highlights the risk of external asymmetric demand shocks due to too strong a dependence on one sector or one customer country. The purpose of this article is to build two indicators of exposure to shocks—sector-based and geographical—taking into account the symmetry of the export structures of a future member with the EMU and the trade openness of the future member. This enables us to draw up a classification of the CEE countries according to fulfillment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…That might lead to asymmetric shocks. In addition, Trotignon (2005) estimated sector-based (diversification or Kenen criterion) and geographical indicators. He concluded that Bulgaria, Slovakia and to a greater extend Estonia and Latvia might experience future asymmetric shocks because of their industrial structure and export patterns.…”
Section: Costs Of Adoptionmentioning
confidence: 99%
“…That might lead to asymmetric shocks. In addition, Trotignon (2005) estimated sector-based (diversification or Kenen criterion) and geographical indicators. He concluded that Bulgaria, Slovakia and to a greater extend Estonia and Latvia might experience future asymmetric shocks because of their industrial structure and export patterns.…”
Section: Costs Of Adoptionmentioning
confidence: 99%